Ontologies representing multidisciplinary decision-making rationales for sustainable infrastructure developments. (February 2022) - Xue, Bin; Chen, Xingbin; Liu, Bingsheng; Zhao, Dong; Zhang, Zheng; Kim, Jung In
Highlights: Two ontologies are developed for multidisciplinary decision-making. A tuple of 〈DMs〉, 〈DC〉, 〈DAs〉, and 〈SPIs〉 is proposed to represent MDM rationales. They specify heterogeneous decision preferences in evaluating sustainability. They are validated using case studies as formal, comprehensive, and reusable. They serve as a decision support system for infrastructure professionals. Abstract: A multidisciplinary decision-making (MDM) process is required for sustainable infrastructure developments in early design stage of integrated project delivery. Decision makers from multiple disciplines employ heterogeneous decision criteria when evaluating decision alternatives for the project developments. This results in uncertainty in alternative prioritization as the scoring ranges of sustainable performance indexes for those alternatives are indistinguishable. This study has formalized the rationales of decision coordinators for converting scores of sustainability performance indexes assessed by decision makers to the normalized ones based on their preferred decision criteria in a consistent and collective manner. Two ontologies have been formalized, which include 45 classes, 119 properties, 50 sub-properties and their facets. The ontologies are validated using three cases of sustainable infrastructure developments. Validation results indicate that they are formal, comprehensive, and reusable in representing MDM rationales, i.e., the interrelationships among decision makers, decision criteria, decision alternatives, and sustainability performance index. Theoretically, these two ontologies contribute to the Triple Bottom Line theory and social choice theory by specifying heterogeneous decision preferences in evaluating sustainable infrastructure developments. For practical implications, the developed ontologies serve as a computer-readable decision support tool to systematically store and communicate MDM information between multidisciplinary professionals in infrastructure project management.